Comprehensive Analysis of Clinical Trials Registration for Lupus Nephritis Therapy on ClinicalTrials.gov - Gao, Yanfang; Wang, Yuhan; Li, Rongshan; Zhou, Xiaoshuang (Frontiers in Medicine, 2021)
Objective: Clinical trials are the most effective ways for evaluating therapeutic strategies. The purpose of this study was to comprehensively assess the characteristics of trials on LN and provide reference for LN treatment and research. Methods: The registered therapeutic trials on drug interventions for LN were obtained from ClinicalTrials.gov as of December 3th, 2020. All registration studies were collected, regardless of their recruitment status, research results, and research type. The general characteristics, methodological characteristics, detailed characteristics, investigated drugs, eligibility criteria and outcome measures of these trials were analyzed. Results: A total of 126 eligible trials were evaluated and half of the trails enrolled less than 50 participants and 69.8% of them included adult subjects only. 70.7% of the trials spanned 6-24 months. Moreover, 95.2% of them adopted interventional study design. Of intervention trials, 56.6% were in phase 2 or phase 3, 76.7% were randomized, 77.5% were parallel assignment and 41.7% were masked. Of all trails, 42.1% were completed, 13.5% listed results at ClinicalTrials.gov and 32.5% trials had web links for the publications of results. Relatively high percentage (23.0%) of trials were terminated or withdrawn. Chemical agents and biologics were the most widely studied immunotherapies, of which mycophenolate mofetil (MMF), cyclophosphamide (CTX), tacrolimus (TAC), and rituximab (RTX) were the most studied. The eligibility criteria and outcome measures of included trials are various and involving a variety of indicators. Conclusions: Most clinical trials for LN therapy registered on ClinicalTrials.gov were randomized, parallel assigned and insufficient masked interventional trails with small scale, short duration, various eligibility criteria and outcome measures. We hope more large-scale, long-term multi-center and high quality RCT trails with standardized inclusion criteria /exclusion criteria and treatment effect evaluation system would be conducted and more energy and fund would be put into exploring biological products and stem cell therapies.